BEGONIA ROBII, A NEW SPECIES OF BEGONIA FROM LIMA PULUH KOTA, WEST SUMATRA - Wisnu Handoyo Ardi; Deden Girmansyah; Mark Hughes (Research Center for Biology, 2021)
ARDI. W.H., GIRMANSYAH, D. & HUGHES, M. 2021. Begonia robii, a new species of Begonia from Lima Puluh Kota, West Sumatra. Reinwardtia 20(1): 37–41. — A new species of Begonia sect. Jackia (Begoniaceae), B. robii Ardi & Girm., is described from West Sumatra and is a limestone karst endemic in the Tanah Datar dan Lima Puluh Kota Regency. Its provisional IUCN threatened category is considered to be Endangered.